STRATEGI PENINGKATAN MUTU PENDIDIKAN DI PERGURUAN TINGGI - Cecep Alba (Jurnal Sosioteknologi, 2011)
If the process of education at an educational institution is correct, then the educational goals will be achieved. If the educational process does not correct, it will be difficult to achieve educational goals. Right education process will be conducted by lecturers who improve the quality of its competence. The quality of faculty competence will increase when the educational climate in which he served conducive to career development. Realizing the climate and atmosphere that support academic career development lecturers become an absolute existence. Keywords: education, competence, conducive, career.